An aerodynamic investigation of a high-pressure turbine using rotor casing static pressure measurements at engine representative conditions with different tip designs, tip gaps and inlet temperature profiles - Singh, D; Beard, PF; Cardwell, D; Staelens, V; Bahulekar, P; Stokes, M; Bather, S; Chana, KS (American Society of Mechanical Engineers, 2024)
A rotating High-Pressure (HP) turbine, in modern aircraft engines, is subjected to high cyclic thermal and mechanical loads. Shroudless turbines experience high heat loads on the rotor tip and casing, which makes them one of the life-limiting components for an engine. If the rotor tip starts to erode, then the tip clearance increases which increases the over-tip leakage flow, resulting in reduced stage efficiency and ultimately, the engine lifetime. Since the 1970s, extensive research has been undertaken to understand the over-tip leakage flow, and develop mitigation strategies such as novel tip designs, to minimize the losses and heat load. However, the majority of the present findings are based on linear cascade or low-speed rotational studies, due to the high cost of the experiments and difficulty in instrumentation at engine conditions. Recent studies (mostly numerical) have shown the importance of testing at engine representative conditions, specifically targeting the transonic tip flow in a high-speed rotational environment, which is essential for an accurate understanding.